Square Script Decoration of Two Temples Belonged to One Banner - Rinchinsambuu, Otgonbaatar (Tibetan Studies, 2025)
It is necessary to consider the Mongolian square script monuments inherited from the great empire period to early 20th century as an old monument and pay attention, collect, check and put into the scientific research circulaltion. In this regard, the temple walls, entrance doors, cabinet and furniture front sides, and other various item decorations have special significances. This time, we are decoding the words written by a square script in the Tibetan language on the door and nearby areas of two temples belonging to one banner as an example and putting them into the scientific research circulation. Hence the letters and inscriptions have peculiar and worth of interest features, we are talking in detail and relevant photos had been attached. Нэгэн хошууны хоёр хийдийн дөрвөлжин үсгийн гоёл Хураангуй: Монголын дөрвөлжин үсгийн дурсгалыг их гүрнээс хойш хэрхэн уламжилсныг хорьдугаар зууны эхэн үе хүртэл бид хуучин дурсгал хэмээн үзэж анхааран цуглуулж нягтлаад эрдэм шинжилгээний гүйлгээнд оруулах нь зохистой. Үүнд сүм хийдийн хана туурга, хаалга үүд, сав шүүгээний нүүр бараг эдлэл хэрэглэлийн зүйл дээрх гоёл чимэглэл онцгой байр суурийг эзэлнэ. Энэ удаа түүний нэг болох нэг хошууны хоёр хийдийн хаалга хатавчны дөрвөлжин үсгээр төвөд хэлээр бичсэн үг үсгийг тайлбарлан судалгааны эргэлтэд оруулж байна. Энэхүү хоёр чимэглэлийн үсэг бичээс нь өвөрмөц сонин онцлогтой болох тухай дэлгэрүүлэн өгүүлж, гэрэл зургийг хавсаргасан болно. Түлхүүр үг: Дөрвөлжин үсэг, сүм хийдийн гоёл, хаалга хатавчны бичээс